2016
DOI: 10.1152/ajpcell.00006.2016
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-19 induces angiogenesis in the absence of hypoxia by direct and indirect immune mechanisms

Abstract: Neovascularization and inflammation are independent biological processes but are linked in response to injury. The role of inflammation-dampening cytokines in the regulation of angiogenesis remains to be clarified. The purpose of this work was to test the hypothesis that IL-19 can induce angiogenesis in the absence of tissue hypoxia and to identify potential mechanisms. Using the aortic ring model of angiogenesis, we found significantly reduced sprouting capacity in aortic rings from IL-19(-/-) compared with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Furthermore, Th17 and Th2 cytokines, including IL-17A, IL-4 and IL-13, induce IL-19 expression in airway epithelial cells [15], where it may be involved in asthma and tissue fibrosis as part of a complex cellular interactions between Th17 cells, Th2 cells and airway epithelial cells. IL-19 is also involved in tissue injury and inflammation, as it induces angiogenesis by promoting proangiogenic genes expression in both endothelial cells and macrophages [31, 32]. …”
Section: Immunobiology Of the Il-20r Cytokinesmentioning
confidence: 99%
“…Furthermore, Th17 and Th2 cytokines, including IL-17A, IL-4 and IL-13, induce IL-19 expression in airway epithelial cells [15], where it may be involved in asthma and tissue fibrosis as part of a complex cellular interactions between Th17 cells, Th2 cells and airway epithelial cells. IL-19 is also involved in tissue injury and inflammation, as it induces angiogenesis by promoting proangiogenic genes expression in both endothelial cells and macrophages [31, 32]. …”
Section: Immunobiology Of the Il-20r Cytokinesmentioning
confidence: 99%
“…Il19 2/2 mice have impaired neovascularization during recovery from murine hindlimb ischemia, which could be rescued by subcutaneous injection of rmIL-19 (6). More recently, we reported that IL-19 could induce angiogenesis in normoxic conditions (7).…”
mentioning
confidence: 93%
“…In our experiments , IL‐19 treatment enhanced protein expression of VEGF in myocardium of mice with MI. An in vivo assay reported that IL‐19(−/−) mice responded to VEGF significantly less than wild‐type mice and demonstrated decreased capillary formation in Matrigel plugs (Kako et al ., ), indicating that IL‐19‐induced angiogenesis was not only dependent on its up‐regulation of VEGF. Macrophages polarized toward an M2 phenotype had a higher angiogenic potential, compared with other macrophage subsets (Zajac et al ., ; Jetten et al ., ).…”
Section: Discussionmentioning
confidence: 96%